Understanding the Drivers of Responsible Consumption: A Conceptual Framework - Das Chatterjee, Arundhati; Sur, Soma (Yayasan Sinergi Kawula Muda, 2025)
Over the years, population explosion and subsequent ever-increasing demand have led to natural resource depletion, wreaking havoc that has left its mark on the environment and threatening human lives. SDG12 aims to achieve responsible consumption that can sustain livelihoods for the present and future generations. However, the notion of responsible consumption is vaguely addressed in existing literature. Understanding the idea of consuming responsibly and its distinct nature as an element of sustainable consumption is important. This study focuses on analysing responsible consumption in the organic food sector and the drivers that motivate it. The study conducts a Bibliometric analysis using the Dimensions.AI database to identify relevant concepts related to responsible consumption and utilises them as a construct for developing a conceptual framework. The study finds that ethical and green consumption are important dimensions of responsible consumption. The study also underscores the role of ethical values in creating green purchase intent and how this intent mediates between value and consumption. Since consumption is a crucial element of human lives, its moderation is important for the success of SDG12 and all other sustainable goals. Environmental awareness and values within oneself contribute to developing purchase intent. During marketing a product, if ethical elements are considered, it may help bridge the intent–behaviour gap.